In vivo Hox binding specificity revealed by systematic changes to a single cis regulatory module. - Sánchez-Higueras, C.; Rastogi, C.; Voutev, R.; Bussemaker, H.J.; Mann, R.S.; Hombría, J.C. (Nature communications, 2019)
Hox proteins belong to a family of transcription factors with similar DNA binding specificities that control animal differentiation along the antero-posterior body axis. Hox proteins are expressed in partially overlapping regions where each one is responsible for the formation of particular organs and structures through the regulation of specific direct downstream targets. Thus, explaining how each Hox protein can selectively control its direct targets from those of another Hox protein is fundamental to understand animal development. Here we analyse a cis regulatory module directly regulated by seven different Drosophila Hox proteins and uncover how different Hox class proteins differentially control its expression. We find that regulation by one or another Hox protein depends on the combination of three modes: Hox-cofactor dependent DNA-binding specificity; Hox-monomer binding sites; and interaction with positive and negative Hox-collaborator proteins. Additionally, we find that similar regulation can be achieved by Amphioxus orthologs, suggesting these three mechanisms are conserved from insects to chordates.